A renovação carismática católica e a elaboração da identidade religiosa dos seus seguidores : desafios e limites dentro do catolicismo - Jesus, José Soares de (2012)
The Catholic Charismatic Renewal has an outstanding presence in the Brazilian Catholicism during the century XX. It is an ecclesial movement that led to several deployments in the configuration of the Catholicism after the Council Vatican II. RCC became elaboration space and of encounter of the religious identity for many Catholic. This research seeks to understand how this phenomenon takes place from the typological concept of "Convert" proposed by Danièle Hervieu-Léger. In this course concerning subjects are approached RCC, going by his/her initial shock with the plurality of the Catholicism transformer sketched by CEBs, besides the institutional Catholicism, and with the Catholicism very strong devocional in Brazil, for his/her appearance and expansion, with prominence for the significance of the coming of the New Communities inside RCC, as well as of the relationship among the characteristics of elaboration of the religious identity, cultivated in RCC and the modernity. The methodology used is preponderantly bibliographic, coupled with the handling of questionnaires that were applied between members of the RCC.